Autonomic support of endurance, strength and speed performance in athletes - S. M. Kanyhina; V. V. Syvolap; M. S. Potapenko (Zaporožskij Medicinskij Žurnal)
Examining the autonomic support of muscular activity in athletes enables an assessment of the ANS impact on achieving a high-level of sports performance at different ages, an identification of interaction patterns between the ANS divisions in the process of short-term and long-term adaptation to muscular load, identifying the features of the cardiovascular system autonomic regulation in athletes training different physical performance